Processing complex surgical instruments in CSPD. Issue 6 (30th November 2015) - Griffin, Janice; McLean, Melvin; Saulan, May
Abstract : Surgical instruments are becoming more complex for newer, minimally-invasive procedures. These instruments benefit patients by making smaller surgical incisions that lead to faster recoveries. But their intricate designs create challenges for maintaining, cleaning, and sterilization.